Dynamics of Tourism and Economic Growth in the Oil-Exporting Economies: A Tri-Variate Causality - Saeed Dehghan Khavari; Seyed Hossein Mirjalili; Saeedeh Derakhsh (International Economics Studies, 2021)
The causality between tourism growth and economic growth would not be very accurate regardless of the environmental factors affecting them such as the oil revenues. The present study investigates the effects of oil revenues on the causality between them, to present the difference between the two variables in oil-exporting countries. We examined the causal relationship using Dumitrescu and Hurlin's model (2012) and the trivariate method in 9 oil-exporting countries from 1996 to 2019. The results show a one-way causal relationship between economic growth and tourism promotion in two variate causality but no relationship was found between them in trivariate. However, one-way causality is weakened when oil revenues are introduced. The causality of economic growth is not confirmed in the presence of oil revenues, as the causal relationship in the two-variable test is affected by the abundance of oil revenues.
Keywords: 330; Tourism; Economic Growth; Oil-exporting Countries; Tri-Variate Causality